Unified Communication and Collaboration System (uNme) - M. Zaidi;; M.D. Fazrul Azlan;; S. Rozanuddin;; Z. Ida Zuraida;; I. Shahnnor;; M.I Shahrol Nizam;; A. Nazrol;; A.Z. Nazri (Universiti Sains Islam Malaysia, 2024)
uNme is a Unified Communication and Collaboration platform. uNme converge video, voice and data to facilitate communication and collaboration at any time, for any where using any device on any network to speed- up business decision & fully developed and owned by TM.